Traditional Healers Approach to the treatment of Puerperal Psychosis (1997)
This paper presents an African (Nigeria) traditional healers approach to the treatment of puerperal psychosis. The authors interviewed the traditional healer. Result shows that such patients are treated in 4 stages: Stage 1: Observation of abnormal behaviours of patient and immediate withdrawal of the baby from the patient, especially if danger for the baby is foreseen by the traditional healer. Stage 2: Oral administration of a mixture of some sedative herbs (Epo mango, Atare, Kan, Ewe Eripo - all mixed with pap). Stage 3: If the origin of the puerperal psychosis is seen by the traditional healer to be a broken taboo or adultery on the part of the patient, the traditional healer takes her to a flowing stream, washes her head with black native soap, while he sings some Incantations. Thereafter oracle consultation and sacrifice to the gods will follow. Stage 4: When patient starts to get better, she is encouraged to start to breast feed the baby and to socialise with the society. The authors conclude by stressing the importance of the knowledge of the cultural beliefs, involvement of the relatives, involvement of some psychotherapeutic components, and reintegration programme in the treatment methods.